2014
DOI: 10.1007/s13277-014-2826-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PSF1 expression inhibits cell proliferation in lung cancer cells in vitro

Abstract: Partner of sld five 1 (PSF1) is a member of the heterotetrameric complex termed GINS. Previous studies have shown that PSF1 is unregulated in several cancer and associated with tumor malignant characters. However, the effects of PSF1 in lung cancer are still unclear. The goal of this study was to investigate the effects of PSF1 on the proliferation capacities of lung cancer. To start with, expression of PSF1 in 22 human lung cancer samples and adjacent non-tumor samples were detected by real-time RT-PCR and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…GINS1 (also known as PSF1 ) is a subunit of the GINS (Go, lchi, Nii, San) complex which drives the unwinding of DNA in front of the replication fork [ 41 ]. Many studies have shown that GINS1 is up-regulated in several cancer types including lung, colon, prostate, colorectal and breast cancers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. It is reported that GINS1 is expressed widely in early embryogenesis in mice, stem and progenitor cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…GINS1 (also known as PSF1 ) is a subunit of the GINS (Go, lchi, Nii, San) complex which drives the unwinding of DNA in front of the replication fork [ 41 ]. Many studies have shown that GINS1 is up-regulated in several cancer types including lung, colon, prostate, colorectal and breast cancers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. It is reported that GINS1 is expressed widely in early embryogenesis in mice, stem and progenitor cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that each GINS member is associated with malignant progression in several different tumor histotypes, i.e., PSF1 for breast cancer 3 , colon cancer 4 , and lung cancer 5 , PSF2 for cholangiocarcinoma 6 , and PSF3 for colon cancer 7 and non-small cell lung cancer 8 . Although we previously reported on the levels of expression of SLD5 in different cancer cell lines 7 , to the best of our knowledge there have been no reports thus far on its expression and malignant tumor progression.…”
mentioning
confidence: 99%
“…Overexpression of the GINS subunits were also reported in cancers. Psf1 was relatively highly expressed in breast tumor and lung cancer cells (Nakahara et al, 2010 ; Zhang J. et al, 2015 ). An increased ability of cancer cells to proliferate by Psf1 overexpression was observed by a mouse xenograft model (Nagahama et al, 2010b ).…”
Section: The Cmg As a Potential Target For Cancer Therapymentioning
confidence: 99%